Effect of Decomposition of CuO Film on Ignition of Organic Explosives by a Laser Pulse; Propellants, Explosives, Pyrotechnics; Vol. 44, iss. 12 - Khaneft A. V. Aleksandr Villivich (2019, 2019)
Title screen